2019
DOI: 10.3390/vaccines7010028
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perceptions of Adverse Events Following Immunization among Healthcare Professionals in Africa: A Case Study from Ghana

Abstract: The spontaneous reporting of suspected adverse events following immunization (AEFI) by healthcare professionals (HCPs) is vital in monitoring post-licensure vaccine safety. The main objective of this study was to assess the knowledge and perceptions of AEFIs among healthcare professionals (HCPs) in Africa, using the situation in Ghana as a case study. The study was of a cross-sectional quantitative design, and was carried out from 1 July 2017 to 31 December 2017 with doctors, pharmacists, and nurses as the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
4
20
1
2
Order By: Relevance
“…The low proportion (32.3%) of respondents with adequate knowledge of HIV exposed/infected infant immunization is similar to the figures from other Nigerian centers (17%-50%), 24 but lower than reports from other parts of Africa (54%-69%) 25 , 26 and Asia (55.6%). 17 , 27 This finding could result in health care workers, who are often considered as trusted sources of health information, serving as conduits for misinformation to HIV-positive mothers regarding recommended vaccines, schedules, and contraindications.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The low proportion (32.3%) of respondents with adequate knowledge of HIV exposed/infected infant immunization is similar to the figures from other Nigerian centers (17%-50%), 24 but lower than reports from other parts of Africa (54%-69%) 25 , 26 and Asia (55.6%). 17 , 27 This finding could result in health care workers, who are often considered as trusted sources of health information, serving as conduits for misinformation to HIV-positive mothers regarding recommended vaccines, schedules, and contraindications.…”
Section: Discussionsupporting
confidence: 71%
“… 35 The predictive role of age and work experience could be attributed to the impact of cumulative experience and in-service training opportunities. Further, the finding of knowledge disparity between the professions, though this conflicts with reports from Ghana, 26 could reflect differences in pre-service curricula, roles, and responsibilities as well as access to continuing education opportunities. 36 …”
Section: Discussionmentioning
confidence: 59%
“…[ 14 ] However, a contrary finding was obtained in another Ghanaian study where majority of the respondents demonstrated good understating of the concept and definition of AEFI. [ 15 ] Though the assessment of the understanding the concept of AEFI was done among mothers of under-fives in this study while the Ghanaian studies had its assessments among health care workers. However, the variation that exists between the studies conducted in Ghana could be attributable to the fact the one of the studies was conducted in a rural district while the others included a mix of health care workers including medical doctors, nurses and pharmacist cutting across all the levels of health care.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] Additionally, other studies carried out in Nigeria, Kenya, Albania and Ghana reported varying level of knowledge of AEFI ranging from poor to fair. [ 9 , 15 , 18 , 19 ] It is important to note that the variation that existed in the levels of knowledge of AEFI could be attributed to the categories of the respondents. While in this study, mothers of under-fives were the subjects and other studies used health care workers of which all but one found the health care workers demonstrating lower levels of knowledge of AEFI than the mothers.…”
Section: Discussionmentioning
confidence: 99%
“…These training protocols cater identification, prevention and treatment of AEFI. 21,24,25 New vaccines: an increasingly complex situation With introduction of new combination vaccines in market the assurance of vaccine quality has become more complex and cumbersome process. As a result, NRA has increased the regulatory requirements for the manufacturers to meet the safety and efficacy criterions.…”
Section: Adverse Events Following Immunization (Aefi)mentioning
confidence: 99%